CERDIK and PATUH method to control hypertension with the interprofessional education and collaboration approaches - Sri Dewi Megayanti; Ni Luh Putu Inca Buntari Agustini; Ida Ayu Ningrat Pangruating Diyu; I Nyoman Widiadnyana; Ni Ketut Erawati; Putu Indah Jelita Lestari; Vinda Eka Budiningsih (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Based on data from the non-communicable disease program at community health centers in 2023, hypertension cases in Pedungan Village, South Denpasar still have the highest number of cases compared to other diseases. Of the existing hypertension cases, only a portion receive health services at the Community Health Center, this is caused by a lack of public knowledge and understanding about controlling hypertension. People with Hypertension must be able to control their blood pressure well to avoid various serious disease complications. To avoid complications that can occur, a person with hypertension needs good knowledge. Knowledge can be increased by providing education. One educational method to increase the knowledge of people with hypertension is the CERDIK and PATUH method. That education method can be provided through collaboration with various parties using the Interprofessional Education (IPE) and Interprofessional Collaboration (IPC) approaches so the education can be provided more comprehensive. The aim to provide CERDIK and PATUH education in efforts to control hypertension using the IPE and IPC approaches. The method use is education through counseling using booklets, audiovisual media, demonstrations, and practice. Based on the pre and post test results, it is stated that providing CERDIK and PATUH education in efforts to control hypertension using the IPE and IPC approaches can increase public knowledge.